Implementasi Dashboard Business Intelligence Penjualan dan Optimasi Stok pada Japri Coffee - Ahmad Luthfi Tedja Wibowo; Farizi Ilham; Desi Fatmawati; Mumu (CV. Shofanah Media Berkah, 2026)
Japri Coffee Kertamukti is a culinary business with high daily transaction volumes, yet it continues to encounter challenges in integrating operational data from point-of-sale applications, CSV files, and manual stock records. These integration issues result in stock inconsistencies and elevated levels of food waste in raw materials. This study focuses on developing a Business Intelligence dashboard to unify operational data and deliver real-time analysis of sales performance and stock management. The research employs the Data Analytics Lifecycle combined with a prototype development model, encompassing requirements analysis, data flow design, dashboard visualization, and the implementation of forecasting and reporting features.